Zdravstvene teškoće i izvori zabrinutosti adolescenata tijekom prilagodbe na srednju školu - Kozjak Mikić, Zlatka; Jokić-Begić, Nataša; Bunjevac, Tomislav (2012)
The transition from primary to secondary school can be stressful, although it is something normative. More intense stress manifestation (e.g. psychosomatic and emotional difficulties) can prevent pupils from achieving academic success, which is their main task at school. The purpose of this survey was to find out the frequency and persistence of psychosomatic and emotional complaints during the first year of secondary school, depending on gender and school track. It was a two wave longitudinal study. In the first measurement there were 308 participants, and in the second measurement 291 participant. Longitudinal data was collected from 266 of them. They were examined by means of Psychosomatic symptoms questionnaire (Vulić-Prtorić, 2005), CORE-YP questionnaire (Twigg and associates, 2009), and Worries domain scale (Kozjak Mikić, 2011). The results were analyzed with multivariate ANOVA. During the first grade of secondary school, 15%-17% of participants had more pronounced psychosomatic and emotional difficulties. Psychosomatic difficulties were relatively mild, and decreased with time, but emotional difficulties were more intense and persistent during the whole first grade. The frequency of health complaints was related to gender and school track. Girls and general-program high school pupils had more health complaints than boys and pupils in trade schools. Furthermore, the frequency of emotional complaints was related to the interaction of gender and school track. High school boys did not significantly differ from girls when displaying emotional difficulties. During the first grade, the main source of worries and stress were academic requirements. Lazarus stress model, as well as Tripartite model of emotions, can explain the results. Early pupil assessment is helpful in avoiding more serious health difficulties if conducted in the first grade of secondary school. It is necessary to make teachers and parents aware of paying attention and taking the appropriate approach to pupils with psychosomatic and emotional adaptation difficulties, which are the practical implications of the study.
ENG